FABP4 Dynamics in Obesity: Discrepancies in Adipose Tissue and Liver Expression Regarding Circulating Plasma Levels - Queipo-Ortuño, María Isabel (Public Library of Science, 2012)
BACKGROUND: FABP4 is predominantly expressed in adipose tissue, and its circulating levels are linked with obesity and a poor atherogenic profile. OBJECTIVE: In patients with a wide BMI range, we analyze FABP4 expression in adipose and hepatic tissues in the settings of obesity and insulin resistance. Associations between FABP4 expression in adipose tissue and the FABP4 plasma level as well as the main adipogenic and lipolytic genes expressed in adipose tissue were also analyzed. METHODS: The expression of several lipogenic, lipolytic, PPAR family and FABP family genes was analyzed by real time PCR. FABP4 protein expression in total adipose tissues and its fractions were determined by western blot. RESULTS: In obesity FABP4 expression was down-regulated (at both mRNA and protein levels), with its levels mainly predicted by ATGL and inversely by the HOMA-IR index. The BMI appeared as the only determinant of the FABP4 variation in both adipose tissue depots. FABP4 plasma levels showed a significant progressive increase according to BMI but no association was detected between FABP4 circulating levels and SAT or VAT FABP4 gene expression. The gene expression of FABP1, FABP4 and FABP5 in hepatic tissue was significantly higher in tissue from the obese IR patients compared to the non-IR group. CONCLUSION: The inverse pattern in FABP4 expression between adipose and hepatic tissue observed in morbid obese patients, regarding the IR context, suggests that both tissues may act in a balanced manner. These differences may help us to understand the discrepancies between circulating plasma levels and adipose tissue expression in obesity.